The cooling effect of pulse imports on price: The case of the pigeon pea in India - Negi, Akanksha; Roy, Devesh (International Food Policy Research Institute, 2015)
The persistent shortfall in India’s production of pulses in the wake of rising demand has led to an increasing volume of imports in the last decade. By bridging the demand–supply gap, imports are aimed at restricting rising domestic prices. However, the extent to which the imports have been successful in controlling domestic prices is a question that remains unanswered. This paper tries to assess the extent and nature of the cooling effect of imports on domestic prices for one of India’s most important pulses—pigeon pea. Using high-frequency, weekly data we find that for the period 2002–2012, pigeon pea imports and domestic prices are cointegrated. In the long run, a 1 percent increase in imports is associated with lowering prices by approximately 3 percent.